Amblyomma cajennense ticks induce immediate hypersensitivity in horses and donkeys - Pablo Juan Szabó, Matias; Carrão Castagnolli, Karina [UNESP]; Álvaro Santana, Danilo; Botelho de Castro, Márcio; Aurélio Romano, Marco (Springer Nature, 2004)
Since host immune reaction to ticks interferes with tick-borne pathogen transmission, it is important to recognize naturally occurring tick-host immune relationships to better understand the epidemiology of such infectious diseases. Amblyomma cajennense is an important tick-borne disease vector in the Neotropical region and horses maintain it in domestic environments. In the present work intradermal testing of A. cajennense tick exposed horses and donkeys using crude tick antigens was used to evaluate the type of hypersensitivity induced by infestations. Animals sensitized by A. cajennense infestation displayed an immediate hypersensitivity reaction at the antigen inoculation site. Foals sensitized with experimental infestations and field sensitized horses presented the most intense reactions (40% of ear thickness increase). Field sensitized donkeys presented less intense reaction reaching no more than 22% of mean thickness increase. Control horses (non-sensitized) had the least intense reaction, with a peak of no more 12% of increase. The presence of a prominent immediate hypersensitivity in equids sensitized experimentally or by field infestations indicates that A. cajennense ticks induce in this host an immune response that is associated with IgE production and which is known to be inappropriate against intracellular pathogens. Differences observed between horses and donkeys are discussed.
Keywords: Amblyomma cajennense; Donkey; Horse; Hypersensitivity; Ixodidae; disease vector; epidemiology; immune response; pathogen; tick; ungulate; animal; animal disease; ear; female; horse; horse disease; immediate type hypersensitivity; immunology; infestation; male; nonparametric test; parasitology; skin test; Animals; Ear; Female; Horse Diseases; Horses; Hypersensitivity, Immediate; Male; Skin Tests; Statistics, Nonparametric; Tick Infestations; Acari; Amblyomma; Animalia; Equidae; Equus asinus; Equus caballus; Ungulata